Pile settlement estimation from CAPWAP analysis - Maung Mya Lin. (2008)
This dissertation is prepared for partial fulfillment of the requirements for the degree of Master of Science in Geotechnical Engineering. The main objective of this study is to assess the reliability of CAPWAP program in the estimation of load settlement behavior of pile.